Funding challenges and successes in arts education - Challons-Lipton, Siulolovao 1965-; Emanuel, Richard 1960- (Advances in educational marketing, administration, and leadership (AEMAL) book series, 2018)
"This book addresses the challenges surrounding the funding of the arts globally, the difficulty educators have faced in attempting to promote the fiscal support of the arts, particularly at the national, legislative level, and innovative ways to fund the arts. It contains resources to help implement fiscal changes that support the funding of the arts in education"--